The management of hypertension — a survey of opinions among general practitioners - Fulton, Mary (1979)
In order to clarify current opinion on aspects of the management of hypertension, a postal questionnaire was sent to all 420 general practitioners in the Lothian Health Board Area. Three hundred and nine doctors (74 per cent) replied. A high proportion were willing to undertake the investigation and follow-up of most hypertensive patients in general practice but there were conflicting opinions on the use of Phase 4 and Phase 5 in the measurement of blood pressure, the number and type of investigations which were appropriate, the level of diastolic blood pressure at which treatment should begin, and the level to which the diastolic blood pressure should be reduced with treatment.